Examining the types and purpose of cloud computing used for library services delivery in academic libraries in Kwara State, Nigeria - Isiaka, Abdullahi Olayinka; Saliu, Abdulfatai; Mahammuod, Sulyman Olaitan; Bankole, Qudus AJibola (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: The implementation and integration of information and communication technology in library services and operations has revolutionized traditional practices, enabling libraries to adapt to the evolving needs of users in the digital era. Purpose: The main purpose of this study is to examine the types and purposes of cloud computing used for library service delivery in academic libraries in Kwara State, Nigeria. Methods: The study used a descriptive survey approach. The population was all the 108 librarians in the eight universities in Kwara State, Nigeria. A total enumeration sampling technique was employed, and a questionnaire was used to collect data from the librarians. The study answered three research questions. Findings: The study revealed that OCLC, Word cat, Google Docs, and other types of cloud computing are being utilized by the librarians. The study also revealed that poor internet connectivity, among other challenges, militates against the use of cloud computing for academic library service delivery. Conclusion: The study concluded that the librarians make use of cloud computing for library services. The study recommends that the library should provide reliable internet facilities with fast speeds, high broadband, and reliable power supplies, among others.